COMPANY PROFILE SD ISLAM KHAIRA UMMAH DALAM MEDIA AUDIO VISUAL - MUHAMMAD LUTHFIE, Dini Faisal, S.Ds., M.Ds., Elya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Promotion of Islamic SD Khaira Ummah that has been done through print media such as banners, brochures, calendars and banners. However, over the times and technology, the promotion can be done anywhere and anytime. So SD Islam Khaira Ummah need a media that will reach a wider audience and make it easier to access audience. Therefore it is necessary to design a media campaign SD Islam Khaira Ummah through audio-visual media where output or outcome happens in the form of a video company profile. Video company profile selected for the presence of these media can facilitate audience in knowing and understanding what is promoted by Islamic SD Khaira Ummah.In designing the company profile Islamic SD Khaira Ummah, the authors collected data through interviews, observation and documentation. After getting the data from SD Islam Khaira Ummah to solve the problems that exist, from the data above, the writer using the SWOT (strenght, Weakness, Opportunity, Threat Because by using the SWOT analysis can compare the strengths and weaknesses of existing on the SD Islam Khaira Ummah. The production stage is carried out in SD Islam Khaira Ummah, the camera uses several shooting techniques, ranging from Aerial Shoot, camera stabilizer and camera movement ..Designing video profileSD Islam Khaira Ummah into its video format can be run by Media Player or Quick Time Player, This design is also supported by the supporting media such as calendars, CD Cover, stickers, CD labels, wall clocks, Pin and Block Note.Keywords: Video Profile, SD Islam Khaira Ummah, Audio visual